Legal Framework on Risk Management for Design Works in Malaysia - Ahmad Rashid, Zultakiyuddin; Adnan, Hamimah; Jusoff, Kamaruzaman (2008)
The construction industry is subject to more risks and uncertainties than many other industries. Construction projects are associated with various aspects of risks, be it risks associated at the feasibility stage, design stage, construction stage and post construction stage. In order to complete the project successfully, the parties involved must be able to manage the risks associated with the project. Although the need and importance of risk management cannot be denied, the practice among the players in the construction industry does not reflect such urgency. There have been a number of cases which resulted in damages and losses, where such damages could have been avoided if proper risk management had been properly administered. In the event where risks still occurred, failure to exercise risk management policies will result in no protection available for the parties. The standard of risk management among the parties involved in a construction project in Malaysia differs from one company to another. This is due to various factors such as a company’s resources for risk management, types and size of the projects and so on. As such there is a need to standardize the practice of risk management among the parties involved to secure the safety and performance of the project. This can be achieved through legal measures, where certain requirements on risk management can be imposed to ensure that the least required practice of risk management is exercised. This is in line with the nature of the law itself, namely to address public safety, security, clarity, flexibility, transparency and adaptability. This paper is meant to look at the risks associated with the design works under the traditional procurement route in Malaysia and the need for the Malaysian law to come up with a framework in ensuring the practice of standard risk management among the architects as lead designers under the traditional procurement system. Certain aspects need to be addressed, as Malaysian law seems to be inadequate in establishing the framework for risk management in relation to design works.